ENHANCING THE EDUCATIONAL PROCESS IN PHYSICAL EDUCATION AND SPORTS THROUGH THE DEVELOPMENT OF SPORTS THEORY - Abbasov Bakhadir Asatillaevich (Modern American Journals, 2026)
This article examines the role of sports theory in enhancing the effectiveness of the educational process in the field of physical education and sports. Sports theory is considered as a fundamental scientific basis that ensures the systematic organization of training, the rational planning of physical loads, and the integration of pedagogical, physiological, and psychological principles into educational practice. The study analyzes how the development and application of sports theory contribute to improving the quality of teaching, fostering students’ cognitive engagement, and forming professional competencies among future specialists in physical education and sports. Particular attention is paid to the interrelation between theoretical knowledge and practical skills, as well as to innovative approaches aimed at modernizing the educational process in accordance with contemporary educational standards. The findings highlight that strengthening the theoretical foundations of sports education leads to more sustainable learning outcomes, higher motivation, and the holistic development of learners.
Keywords: Sports theory, physical education, educational process, pedagogical innovation, professional competence, training methodology, physical development.